An Exploratory Discussion on Electric Cars and Sustainable Innovation - Hiroko Oe; Mohd Noman Abdullah (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
This study provides an exploratory discussion to reveal the authors’ perspectives regarding previous academic discussions. In combination with the development of innovative environmentally friendly products, electric vehicles will continue to be an important research topic in the field of innovation. Currently, given the unprecedented challenge of COVID-19, humanity has been charged with the task of developing sustainable business strategies and promoting environmentally friendly business practices. The research surrounding electric vehicles, an important example of innovation, has been enriched by many academic discussions, but it remains important to critically evaluate the development concept of electric vehicles from the perspective of innovation novelty, to examine the factors that support the innovation and to identify issues for future discussions and research. Accordingly, this exploratory study unravels the debate on innovation surrounding electric vehicles and proposes several key issues for future research. Electric vehicles are a new product characterised by two major features ¬– innovation and sustainability – and their development is coupled with a growing interest in environmental issues. Based on the authors’ observations, this study identifies the key factors that support the growth of the industry and presents arguments for reconciling the themes of research and development acceptability and sustainability. It is hoped that the key issues presented in this paper will serve as an effective guide for future research.